REMOTE HOLTER LONGITUDINAL MONITORING - PROMISING DIRECTION IN TELEHEALTH DEVELOPMENT - Y. N. Gorozhantsev; S. G. Sergienko; E. A. Vorotynsteva; Y. V. Emelyanenko (Инновационная медицина Кубани, 2019)
The aim of the telehealth project is to study possible performance of remote analysis of Holter outcomes. We present experience of of our institution and remore Holter monitoring fulfillment. We studied diagnostic advantages of its remote performance. We used portable recorders and proprietary software. Analysis was performed by three physicians of the functional diagnosis department, Scientific Research Institute - Ochapovsky Regional Clinic Hospital #1. By present we performed more 2000 examinations. Clinical cases demonstrating advantages of remote Holter monitoring are described. We discussed perspective of this direction of telehealth. To this system 25 stations of registration devices were connected up in cities and territories of Krasnodar region. We apply 30 cardio-recorders of various producers. Thus, in Krasnodar region the full-scale system of remote Holter monitoring functions and advances now and this has been reached due to active introduction of modern innovative technologies in the field of communication, informatics and development of the software.